Partial replacement of Portland cement with industrial glass waste in mortars - Lopes,Raduan Krause (2021)
Abstract The necessity to reduce the consumption of cement in cementitious composites is a worldwide concern and the partial replacement of cement with industrial waste has gathered considerable interest. One type of industrial waste is glass, which is rich in amorphous silica but can present problems with its use due to the alkali-silica reaction (ASR). The objective of this study was to analyze the compressive strengths of mortars using ground glass residue (GLR). Milling times of 16 h and 32 h were conducted and GLR tested in cement substitutions of 10 w.t.%, 15 w.t.% and 20 w.t.%. A statistical analysis was performed to verify which factors affected mortar strength. The mitigating effect of GLR in ASR was also tested. Results showed that milling time did not affect resistance significantly but w.t.% substitution did. The substitution of 20 w.t.% proved to provide the best result as it was statistically equal to the standard mixture.